2022
DOI: 10.1002/jac5.1669
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Black pharmacists to promote equity in COVID‐19 vaccine uptake within Black communities: A framework for researchers and clinicians

Abstract: Black Americans are disproportionately represented among coronavirus disease 2019 (COVID‐19)‐related morbidities and mortalities. While the COVID‐19 vaccines are positioned to change this disparity, vaccine hesitancy, attributed to decades of systemic racism and mistreatment by the United States health care system, heavily exists among this racially and ethnically minoritized group. In addition, social determinants of health within Black communities including the lack of health care access and inequitable COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Abdul-Mutakabbir et al [ 66 ] initiated a multi-tiered community approach to be effective, whereby faith leaders engaged with the academic community to disseminate COVID-19 information, culturally representative healthcare professionals delivered educational webinars, and used low barrier access sites, to target back communities; Peteet et al [ 80 ], also found an increase in willingness to get vaccinated after a webinar.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdul-Mutakabbir et al [ 66 ] initiated a multi-tiered community approach to be effective, whereby faith leaders engaged with the academic community to disseminate COVID-19 information, culturally representative healthcare professionals delivered educational webinars, and used low barrier access sites, to target back communities; Peteet et al [ 80 ], also found an increase in willingness to get vaccinated after a webinar.…”
Section: Resultsmentioning
confidence: 99%
“…Black pharmacists, for example, recognize the structural and systemic issues that have contributed to the lower vaccination rates in Black communities. By collaborating with community leaders to disseminate evidenced-based information and by advocating and working to increase vaccine access, they can actively work to reduce vaccine inequities [ 66 ]. Furthermore, more effective therapeutic relationships and improved healthcare occur with racial concordance, which emphasizes the importance of racial diversity in healthcare as well as cultural humility [ 130 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there is evidence that racially concordant care between healthcare providers and patients has been associated with improvements in patient communication, which can have implications on medication adherence and health literacy. In this issue of JACCP , Abdul‐Mutakabbir and colleagues highlight this in their inspiring work on the role of Black pharmacists and COVID‐19 vaccination efforts in the Black community 11 . Building upon this concept, we consider it prudent for pharmacy schools and pharmacy residency programs to be thoughtful to consider whether their program demographics are consistent with the community and patient population they serve.…”
Section: Improving the Quality Of Pharmacotherapymentioning
confidence: 99%
“…In this issue of JACCP, Abdul-Mutakabbir and colleagues highlight this in their inspiring work on the role of Black pharmacists and COVID-19 vaccination efforts in the Black community. 11 Building upon this concept, we consider it prudent for pharmacy schools and pharmacy residency programs to be thoughtful to consider whether their program demographics are consistent with the community and patient population they serve.…”
Section: Improving the Quality Of Pharmacotherapymentioning
confidence: 99%